Factors Associated with Diabetic Peripheral Neuropathy among Patients with Type 2 Diabetes Mellitus in Surakarta, Central Java - Azmiardi, Akhmad; Tamtomo, Didik; Murti, Bhisma (Indonesian Journal of Medicine, 2019)
Background: Peripheral neuropathy is the most common chronic complication and often occurs in diabetes mellitus. Peripheral neuropathy can cause morbidity, decreased quality of life,and mortality. This study aimed to analyze the determinants of peripheral neuropathy in patients with type 2 diabetes mellitus in Surakarta, Central Java.Subjects and Method: This study was an observational analytic with cross sectional design. This study was conducted at Surakarta Regional Hospital, Central Java on July 2019. A total of 200 type 2 diabetes mellitus outpatients was selected by simple random sampling. The dependent variable was peripheral neuropathy. The independent variables were age, education level, income, self-efficacy, diet, medication adherence, physical activity, health literacy, duration of illness, and fasting blood sugar. Peripheral neuropathy was measured using the Michigan Neu-black Screening Instrument (MNSI). Other variable data were obtained using questionnaires. Analysis of data used multiple logistic regression.Results: The risk of peripheral neuropathy increased with age of  ?55 years (b = 3.61; 95% CI = 1.51 to 5.70; p= 0.001), duration of illness ? 5 years (b = 2.78; 95% CI = 0.51 to 5.04; p = 0.016 ), and fasting sugar ?110 mg / dL (b= 1.64; 95% CI= -0.01 to 3.03; p= 0.052). The risk of peripheral neuropathy decreased with education level ?senior high school (b= -2.41; 95% CI = -4.31 to -0.51; p= 0.013), income ? Rp 1,800,000 (b= -1.58; 95% CI= -3.12 to -0.04; p = 0.044), high self-efficacy (b= -1.67; 95% CI= -3.26 to -0.07; p= 0.040), controlled diet (b= -1.89; 95% CI= -3.64 to -0.14; p= 0.034), high medication adherence (b= -2.34; 95% CI= -4.13 to -0.56; p= 0.010), high physical activity (b= -2.33; 95% CI= -4.17 to -0.49; p = 0.013), and high health literacy (b= -1.52; 95% CI = -3.18 to 0.14; p = 0.073).Conclusion: The risk of peripheral neuropathy increases with age of ?55 years, duration of illness ? 5 years, and fasting blood sugar ? 110 mg/dL. The risk of peripheral neuropathy decreases with a high education level, income of ?1,800,000, high self-efficacy, controlled diet, high medication adherence, high physical activity, and high health literacy.Keywords: peripheral neuropathy, diabetesCorrespondence: Akhmad Azmiardi. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java, Indonesia. Email: aazmiardi@gmail.com.Mobile: 085245412021 Indonesian Journal of Medicine (2019), 4(4): 300-312https://doi.org/10.26911/theijmed.2019.04.04.02